Swallowing Dysfunction and its Impact on Patients Undergoing Oncological Treatment - Chaudhry, Sharjeel; Ehtesham, Zarmina (Asian Pacific Journal of Cancer Care, 2022)
The effectiveness of head and neck cancer HNC treatments has increased tumour survival, response, and loco-regional control. Treatment escalation does, however, also result in late early and early toxicities. One underrated symptom of HNC patients is dysphagia. Aspiration, dehydration, pneumonia, and malnutrition can all result from swallowing difficulties. About one-third of individuals with dysphagia required therapy for pneumonia. Undiagnosed dysphagia significantly lowers the quality of life, increased death, and caused severe morbidity. In this article, we emphasise the definition, underlying causes, and prognostic factors of dysphagia while also outlining some keys. Better symptoms and cancer therapy may result from a proper evaluation.